Selected Exercises in Particle and Nuclear Physics - Bianchini, Lorenzo (UNITEXT for Physics,, 2018)
This book presents more than 300 exercises, with guided solutions, on topics that span both the experimental and the theoretical aspects of particle physics. The exercises are organized by subject, covering kinematics, interactions of particles with matter, particle detectors, hadrons and resonances, electroweak interactions and flavor physics, statistics and data analysis, and accelerators and beam dynamics. Some 200 of the exercises, including 50 in multiple-choice format, derive from exams set by the Italian National Institute for Nuclear Research (INFN) over the past decade to select its scientific staff of experimental researchers. The remainder comprise problems taken from the undergraduate classes at ETH Zurich or inspired by classic textbooks. Whenever appropriate, in-depth information is provided on the source of the problem, and readers will also benefit from the inclusion of bibliographic details and short dissertations on particular topics. This book is an ideal complement to textbooks on experimental and theoretical particle physics and will enable students to evaluate their knowledge and preparedness for exams. .